Self-reflection and Education of the Emotions for Democracy. Interview to Martha Nussbaum - Modzelewski, Helena (2014)
The education of the emotions is a valuable tool not always taken into account in the development of the democratic, egalitarian background essential to empower citizens. Perhaps the difficulty lies in the fact that, firstly, it is necessary to probe the possibilities of educability of emotions. Martha Nussbaum is one of the contemporary philosophers who have devoted much of their work to the study of emotions, and from her theory, conclusions can be drawn about the question of their educability. Her theory of emotions can be situated within a set of theories that understand emotions as cognitive, which turns literature into a useful tool for their education. However, the author does not put forward an explicit methodology for such development from narrative. To this end, in this interview Nussbaum is asked about the concept of self-conscious reflection as a feasible proposal to enable the education of emotions, as well as about whether a list of “democratic emotions” can be built from her theory. Also, in this context, Nussbaum responds and elaborates on these themes.